Synthesis of oxygen permeable perovskite with small crystallite - Teo, Bryan Ting Guan. (2009)
Ba0.5Sr0.5Co0.8Fe0.2O3-δ(BSCF), a mixed oxygen ionic and electronic conducting ceramic,has been successfully applied as a membrane reactor material for the partial oxidation of methane to syngas reaction. The microstructure of the end product plays an important role in the application, which can be achieved by using small crystallite perovskite powders as starting materials. This project explored various synthesis methods to reduce BSCF powder size. They were prepared by three main methods, namely, EDTA- citrate acid (EC), glycine nitrates (GN) and low temperature hydrothermal urea precipitation process (LTHU). Seeding and concentrated nitric acid treatments were also employed in EC and GN methods to investigate their effects on synthesized powder. The structural and morphological properties of BSCF powders were characterized by XRD and SEM. Results showed that powders prepared by EC and GN agglomerated and gave micronsized particles after calcination at 950°C for 2–4 hours in air. Notably, powders prepared by LTHU, exhibited particle size in the sub- micron level of 0.5 μm subsequent to calcination at 950°C for 10 hours in air. LTHU method developed here show promising results for future research in synthesizing BSCF nano powders.